2021
DOI: 10.4103/jfmpc.jfmpc_2313_20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of spousal violence among married women in a rural area in North Kerala

Abstract: Background: Domestic violence has substantial public health consequences. More than one-third of women globally suffer from physical and sexual violence, mostly by an intimate partner with a lifetime prevalence of 10%–69%. In India, 28.8% of the ever-married women in the reproductive age group, reported domestic violence. Although Kerala, in southern India, performs better than other Indian states on a host of human development indicators for women, 15.8% among the women in this group have ever ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The dominant nature of elder male partner may influence violence as studies show that length of marriage, age difference of the couple, and type of marriage may all be precipitating factors. [ 16 , 17 ] Though education status has variably been associated with domestic violence,[ 16 , 18 , 24 ] literate and employed women were at increased risk of domestic violence in this study. This may be attributed to the fact that literate employed women are more outspoken that they disclose domestic violence in comparison to illiterate unemployed women, or high self-esteem in literate employed women may result in more domestic violence.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The dominant nature of elder male partner may influence violence as studies show that length of marriage, age difference of the couple, and type of marriage may all be precipitating factors. [ 16 , 17 ] Though education status has variably been associated with domestic violence,[ 16 , 18 , 24 ] literate and employed women were at increased risk of domestic violence in this study. This may be attributed to the fact that literate employed women are more outspoken that they disclose domestic violence in comparison to illiterate unemployed women, or high self-esteem in literate employed women may result in more domestic violence.…”
Section: Discussionmentioning
confidence: 71%
“…[ 27 ] These findings are similar to the findings of other studies conducted across different study settings. [ 16 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, 31.8% of women aged between 15 and 24 years reported that they had been exposed to controlling behavior of their husbands ( Nasrullah et al, 2014 ). In Myanmar, 30.2% of women have been determined as being exposed to controlling behavior ( Tun and Ostergren, 2020 ), while it was 39.7% for women in North Kerala, India ( Mundodan et al, 2021 ).…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%